Themes of Anthropology, Autoethnography and Anti-Racist Pedagogies at a Peruvian University - Silva, Marcos Antonio Batista da (2024)
This article analyzes the ethnic-racial debate proposed by the subject «Topics I: Race, Ethnicity and (Counter)Mestizaje in Peru’s Bicentennial», in the Bachelor of Anthropology of the Faculty of Social Sciences of a public university in the capital of Peru, Lima, carried out in 2021. The theoretical-methodological debate is anchored in the theory of ethnic-racial relations on the production of knowledge around race, racism, anti-racism, miscegenation and other recurring themes. The work focuses on a reflection on issues of race, racism and anti-racism in a course taught by the author as a guest professor in collaboration with another professor at the institution. With the participation, the author can reflect with students on how to produce knowledge about race, racism, and anti-racism from a perspective of critical autoethnography oriented toward antiracist education. The work carried out indicates that the course provided the possibility of immersion in multiple debates, concept proposals, theoretical analyzes and historical experiences to address issues related, in particular, with race, racism and anti-racism in higher education in Peru in favor of anti-racist education.